2013
DOI: 10.1029/2012ja018001
|View full text |Cite
|
Sign up to set email alerts
|

Ground and satellite observations of low‐latitude red auroras at the initial phase of magnetic storms

Abstract: [1] We report ground and satellite observations of unique low-latitude red auroras that appear at the initial phase of geomagnetic storms. For two events on 21 October 2001, and 6 April 2000, the low-latitude red auroras appeared at~45 MLAT (L $ 2) $ 1.5 h after the storm sudden commencement in the postmidnight sector in Japan. Comprehensive satellite data were available for the former event. The energetic neutral atom images obtained by the Imager for Magnetopause-to-Aurora Global Exploration satellite show r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…It has been shown that SAR arcs occur during the recovery phase of geomagnetic storms (e.g., Kozyra et al, 1987;Mendillo et al, 2016;Rees & Roble, 1975). Shiokawa et al (2013) reported red aurora that seemed to be SAR arc at low latitudes in Japan when the ring current developed at the beginning of a magnetic storm. Baumgardner et al (2007) reported a rare SAR arc with a very bright intensity reaching 13,000 Rayleigh.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SAR arcs occur during the recovery phase of geomagnetic storms (e.g., Kozyra et al, 1987;Mendillo et al, 2016;Rees & Roble, 1975). Shiokawa et al (2013) reported red aurora that seemed to be SAR arc at low latitudes in Japan when the ring current developed at the beginning of a magnetic storm. Baumgardner et al (2007) reported a rare SAR arc with a very bright intensity reaching 13,000 Rayleigh.…”
Section: Introductionmentioning
confidence: 99%
“…It was reviewed recently within the context of red aurora at midlatitudes by Shiokawa et al . []. Our goal is to use the event of 2 October 2013 to illuminate further, and as quantitatively as possible, the multiple modes of inner‐magnetosphere coupling to the subauroral ionosphere, some of which are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical correlations of ionospheric storms with IpsDst and other parameters will be obtained using the ionospheric peak electron density (NmF2) (Shiokawa et al, 2005) will be used for investigating the intensity of the low-latitude auroras with IpsDst and other parameters. Though the auroral observations were made at midlatitudes, we use the phrase "low-latitude aurora" implying that they occur at much lower latitudes than normal auroras and to be consistent with earlier studies (e.g., Shiokawa et al, 2005Shiokawa et al, , 2013.…”
Section: Data and Analysismentioning
confidence: 59%